Core outcome set and measures of chest health in children and young people with cerebral palsy in the community setting: the CHESTI study protocol - Jos Latour; Noula Gibson; Harriet Shannon; Christopher Morris; Paul McNamara; Diane Sellers; Rachel Rapson; Madeline Pilbury; Samantha Grace; Laura Lowndes; Julia Melluish; Rachel Knight Lozano; et al. (BMJ Open)
Introduction Poor chest health is the leading cause of early mortality in children with cerebral palsy (CP). It is also the most common reason to seek healthcare, accruing significant costs and reducing quality-of-life for children and families. Clinical trials examining chest health interventions in CP are characterised by inconsistent outcome measures, limiting the capacity for evidence synthesis to inform clinical application. The study aims to develop a core outcome set (COS) and related measurement instruments to assess, monitor and evaluate chest health in children with CP, both in research and routine clinical practice. The COS will reflect the views of children, young people, parent/carers, clinicians and researchers, emphasising under-represented groups in research and those at risk of poorer chest health.Methods and analysis A 3-phase methodology will be conducted in line with the Core Outcome Measures in Effectiveness Trials (COMET) Initiative. (1) Candidate outcomes will be identified through a qualitative evidence synthesis and interviews with key stakeholders. Findings will be mapped to COMET-taxonomy, generating a list of candidate outcomes. (2) An international e-Delphi survey will invite stakeholders to rate the importance of each outcome, followed by a consensus meeting to ratify the COS. (3) A structured review, guided by health measurement taxonomy, will evaluate relevant instruments, with a final meeting to agree on recommended measures for each COS domain.Ethics and dissemination Ethical approval was provided by the University of Plymouth Research Ethics Committee for the qualitative interview study (ID5116), e-Delphi study and consensus meeting (ID5636). Study findings will be published open access in a peer-reviewed journal and presented at relevant national and international conferences.Study registration COMET registration: 2590 (https://www.comet-initiative.org/Studies/Details/2590)PROSPERO registration number CRD42024562735.